Preparation method of large-particle aluminum-doped cobaltosic oxide

CN119528226AInactive Publication Date: 2025-02-28YANGJIANG FEDERAL METAL CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411738602.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-28
Estimated Expiration
Not applicable · inactive patent
Patent Text Reader

Abstract

The invention relates to a preparation method of large-particle aluminum-doped cobaltosic oxide, and belongs to the technical field of cobaltosic oxide preparation. The preparation method comprises the following steps: in a stirring state, adding a strong alkali solution into a cobalt salt solution to carry out precipitation reaction, and carrying out solid-liquid separation, washing and drying to obtain a preform; drying the preform, mixing in deionized water, adding chitosan, carrying out ultrasonic treatment, carrying out solid-liquid separation, and drying to obtain an intermediate; and placing the intermediate in absolute ethyl alcohol, adding a coupling agent, stirring and mixing, then carrying out solid-liquid separation, carrying out alcohol washing, drying, and calcining to obtain the composite material. Cobalt hydroxide particles are dried to form more microporous structures, small-molecule chitosan and cobalt hydroxide form a self-loading structure, the grafting rate between an aluminate coupling agent and the cobalt hydroxide particles is increased, cobaltosic oxide with the surface doped with an aluminum oxide layer and rich pore structures is generated through roasting, the specific surface area of the cobaltosic oxide is increased, and the specific surface area of the cobaltosic oxide is increased. The formation of a large-particle structure is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cobalt tetroxide preparation and relates to a method for preparing large-particle aluminum-doped cobalt tetroxide. Background Art

[0002] Lithium cobalt salt is the main component of 3C battery positive electrode materials. With the continuous improvement of social living standards, the specific energy requirements of 3C batteries have also increased accordingly. For example, consumers expect 3C electronic products to have longer standby time and higher safety performance. Therefore, the development of large-capacity, high-power lithium-ion batteries has become an inevitable direction for the development of 3C electronic products.

[0003] In the technical path to achieve high capacity of 3C lithium batteries, the industry has generally recognized two methods: first, using high-nickel ternary precursor materials as positive electrode materials; second, preparing lithium cobaltate precursors with a wide particle size distribution. Although high-nickel ternary precursor materials have high original capacity characteristics, their safety performance needs to be further improved, so they have not yet been widely used in the 3C electronics industry. Lithium cobaltate precursors with a wide particle size distribution need to be carefully designed and adjusted to obtain a particle size distribution that meets the requirements, thereby achieving a high compaction density and meeting the high capacity requirements of 3C batteries. In addition, aluminum-doped cobalt tetroxide products can improve the charging voltage and cycle performance of lithium cobaltate, so the market demand for aluminum-doped cobalt tetroxide is gradually emerging. At present, research on how to prepare aluminum-doped cobalt tetroxide has become the focus of industry attention. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method of large-particle aluminum-doped cobalt oxide. The present invention dries cobalt hydroxide particles to form more microporous structures, forms a self-assembled structure with small molecular chitosan and cobalt hydroxide, increases the grafting rate between the aluminate coupling agent and the cobalt hydroxide particles, and while calcining to generate cobalt oxide with more pore structures, dopes an aluminum oxide layer on the surface to increase its specific surface area and promote the formation of a large particle structure.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing large-particle aluminum-doped cobalt oxide, the preparation method comprising the following steps:

[0007] Step 1) adding a strong alkali solution to a cobalt salt solution under stirring to perform a precipitation reaction, performing solid-liquid separation after the reaction is completed, washing to neutrality, and drying to obtain a preform;

[0008] Step 2) drying the preform, mixing it in deionized water, adding chitosan, ultrasonically treating it, performing solid-liquid separation, and drying it to obtain an intermediate;

[0009] Step 3) placing the intermediate in anhydrous ethanol, adding a coupling agent, stirring and mixing, and then performing solid-liquid separation, washing with alcohol, drying, and calcining to obtain aluminum-doped cobalt tetroxide.

[0010] As a preferred technical solution of the present invention, in step 1), the stirring is carried out at a rotation speed of 300-400 r / min.

[0011] As a preferred technical solution of the present invention, in step 1), the drying is performed at a temperature of 70-80° C. to a constant weight.

[0012] As a preferred technical solution of the present invention, in step 1), the concentration of cobalt ions in the cobalt salt solution is 1.5-2.0 mol / L.

[0013] As a preferred technical solution of the present invention, in step 1), the volume ratio of the cobalt salt solution to the strong alkali solution is 1:1.

[0014] As a preferred technical solution of the present invention, in step 1), the cobalt salt solution is one or both of a cobalt chloride aqueous solution and a cobalt nitrate aqueous solution.

[0015] As a preferred technical solution of the present invention, in step 1), the strong alkaline solution is a sodium hydroxide aqueous solution with a concentration of 1.0-1.5 mol / L.

[0016] As a preferred technical solution of the present invention, in step 2), the drying is performed at a temperature of 150-160° C. for 1.2-1.5 hours.

[0017] As a preferred technical solution of the present invention, in step 2), the ultrasonic treatment is performed at a frequency of 1000-1200W and a temperature of 25-28°C for 45-60min.

[0018] As a preferred technical solution of the present invention, in step 2), the mass ratio of the preform, deionized water and chitosan is 8.0-8.5:900-1000:1.0-1.3.

[0019] As a preferred technical solution of the present invention, in step 3), the stirring and mixing is performed at a temperature of 40-50° C. for 6-8 hours.

[0020] As a preferred technical solution of the present invention, in step 3), the alcohol washing is performed by washing with anhydrous ethanol for 4 times.

[0021] As a preferred technical solution of the present invention, in step 3), the drying is performed at a temperature of 100-110° C. for 2-3 hours.

[0022] As a preferred technical solution of the present invention, in step 3), the calcination is carried out at a temperature of 520-600° C. for 3-4 hours.

[0023] As a preferred technical solution of the present invention, in step 3), the mass ratio of the intermediate, anhydrous ethanol and coupling agent is 12-15:50-60:2-3.

[0024] As a preferred technical solution of the present invention, in step 3), the coupling agent is aluminate coupling agent DL411.

[0025] Beneficial effects of the present invention:

[0026] The present invention dries cobalt hydroxide particles to form more microporous structures, small molecule chitosan and cobalt hydroxide form a self-assembled structure, the grafting rate between the aluminate coupling agent and the cobalt hydroxide particles is increased, and while calcining to generate cobalt tetroxide with more pore structures, an aluminum oxide layer is doped on the surface to increase its specific surface area and promote the formation of a large particle structure. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] Example 1

[0029] A method for preparing large-particle aluminum-doped cobalt oxide, the preparation method comprising the following steps:

[0030] Step 1) adding a strong alkali solution to a cobalt salt solution under stirring to perform a precipitation reaction, performing solid-liquid separation after the reaction is completed, washing to neutrality, and drying to obtain a preform;

[0031] Step 2) drying the preform, mixing it in deionized water, adding chitosan, ultrasonically treating it, performing solid-liquid separation, and drying it to obtain an intermediate;

[0032] Step 3) placing the intermediate in anhydrous ethanol, adding a coupling agent, stirring and mixing, and then performing solid-liquid separation, washing with alcohol, drying, and calcining to obtain aluminum-doped cobalt tetroxide.

[0033] In step 1), the stirring is performed at a rotation speed of 300 r / min; and the drying is performed at a temperature of 70° C. to a constant weight.

[0034] In step 1), the concentration of cobalt ions in the cobalt salt solution is 1.5 mol / L; the volume ratio of the cobalt salt solution to the strong alkali solution is 1:1; the cobalt salt solution is a cobalt chloride aqueous solution; and the strong alkali solution is a sodium hydroxide aqueous solution with a concentration of 1.0 mol / L.

[0035] In step 2), the drying is performed at 150° C. for 1.2 h.

[0036] In step 2), the ultrasonic treatment is performed at a frequency of 1000 W and a temperature of 25° C. for 45 min.

[0037] In step 2), the mass ratio of the preform, deionized water and chitosan is 8.0:900:1.0.

[0038] In step 3), the stirring and mixing is performed at 40° C. for 6 hours; the alcohol washing is performed by washing with anhydrous ethanol for 4 times; the drying is performed at 100° C. for 2 hours; and the calcination is performed at 520° C. for 3 hours.

[0039] In step 3), the mass ratio of the intermediate, anhydrous ethanol and coupling agent is 12:50:2; the coupling agent is aluminate coupling agent DL411.

[0040] Example 2

[0041] A method for preparing large-particle aluminum-doped cobalt oxide, the preparation method comprising the following steps:

[0042] Step 1) adding a strong alkali solution to a cobalt salt solution under stirring to perform a precipitation reaction, performing solid-liquid separation after the reaction is completed, washing to neutrality, and drying to obtain a preform;

[0043] Step 2) drying the preform, mixing it in deionized water, adding chitosan, ultrasonically treating it, performing solid-liquid separation, and drying it to obtain an intermediate;

[0044] Step 3) placing the intermediate in anhydrous ethanol, adding a coupling agent, stirring and mixing, and then performing solid-liquid separation, washing with alcohol, drying, and calcining to obtain aluminum-doped cobalt tetroxide.

[0045] In step 1), the stirring is performed at a rotation speed of 330 r / min; and the drying is performed at a temperature of 75° C. to a constant weight.

[0046] In step 1), the concentration of cobalt ions in the cobalt salt solution is 1.7 mol / L; the volume ratio of the cobalt salt solution to the strong alkali solution is 1:1; the cobalt salt solution is a cobalt chloride aqueous solution; and the strong alkali solution is a sodium hydroxide aqueous solution with a concentration of 1.2 mol / L.

[0047] In step 2), the drying is performed at 153° C. for 1.5 h.

[0048] In step 2), the ultrasonic treatment is performed at a frequency of 1060 W and a temperature of 26° C. for 50 min.

[0049] In step 2), the mass ratio of the preform, deionized water and chitosan is 8.2:933:1.1.

[0050] In step 3), the stirring and mixing is performed at 43°C for 6.5 hours; the alcohol washing is performed 4 times with anhydrous ethanol; the drying is performed at 103°C for 2.5 hours; and the calcination is performed at 540°C for 3.5 hours.

[0051] In step 3), the mass ratio of the intermediate, anhydrous ethanol and coupling agent is 13:53:2.3; the coupling agent is aluminate coupling agent DL411.

[0052] Example 3

[0053] A method for preparing large-particle aluminum-doped cobalt oxide, the preparation method comprising the following steps:

[0054] Step 1) adding a strong alkali solution to a cobalt salt solution under stirring to perform a precipitation reaction, performing solid-liquid separation after the reaction is completed, washing to neutrality, and drying to obtain a preform;

[0055] Step 2) drying the preform, mixing it in deionized water, adding chitosan, ultrasonically treating it, performing solid-liquid separation, and drying it to obtain an intermediate;

[0056] Step 3) placing the intermediate in anhydrous ethanol, adding a coupling agent, stirring and mixing, and then performing solid-liquid separation, washing with alcohol, drying, and calcining to obtain aluminum-doped cobalt tetroxide.

[0057] In step 1), the stirring is performed at a rotation speed of 360 r / min; and the drying is performed at a temperature of 78° C. to a constant weight.

[0058] In step 1), the concentration of cobalt ions in the cobalt salt solution is 1.8 mol / L; the volume ratio of the cobalt salt solution to the strong alkali solution is 1:1; the cobalt salt solution is a cobalt chloride aqueous solution; and the strong alkali solution is a sodium hydroxide aqueous solution with a concentration of 1.3 mol / L.

[0059] In step 2), the drying is performed at 155° C. for 1.5 h.

[0060] In step 2), the ultrasonic treatment is performed at a frequency of 1130 W and a temperature of 27° C. for 55 min.

[0061] In step 2), the mass ratio of the preform, deionized water and chitosan is 8.3:970:1.2.

[0062] In step 3), the stirring and mixing is performed at 47°C for 7.5 hours; the alcohol washing is performed 4 times with anhydrous ethanol; the drying is performed at 107°C for 2.5 hours; and the calcination is performed at 570°C for 3.5 hours.

[0063] In step 3), the mass ratio of the intermediate, anhydrous ethanol and coupling agent is 14:57:2.7; the coupling agent is aluminate coupling agent DL411.

[0064] Example 4

[0065] A method for preparing large-particle aluminum-doped cobalt oxide, the method comprising the following steps:

[0066] Step 1) adding a strong alkali solution to a cobalt salt solution under stirring to perform a precipitation reaction, performing solid-liquid separation after the reaction is completed, washing to neutrality, and drying to obtain a preform;

[0067] Step 2) drying the preform, mixing it in deionized water, adding chitosan, ultrasonically treating it, performing solid-liquid separation, and drying it to obtain an intermediate;

[0068] Step 3) placing the intermediate in anhydrous ethanol, adding a coupling agent, stirring and mixing, and then performing solid-liquid separation, washing with alcohol, drying, and calcining to obtain aluminum-doped cobalt tetroxide.

[0069] In step 1), the stirring is performed at a rotation speed of 400 r / min; and the drying is performed at a temperature of 80° C. to a constant weight.

[0070] In step 1), the concentration of cobalt ions in the cobalt salt solution is 2.0 mol / L; the volume ratio of the cobalt salt solution to the strong alkali solution is 1:1; the cobalt salt solution is a cobalt chloride aqueous solution; and the strong alkali solution is a sodium hydroxide aqueous solution with a concentration of 1.5 mol / L.

[0071] In step 2), the drying is performed at 160° C. for 1.5 h.

[0072] In step 2), the ultrasonic treatment is performed at a frequency of 1200 W and a temperature of 28° C. for 60 min.

[0073] In step 2), the mass ratio of the preform, deionized water and chitosan is 8.5:1000:1.3.

[0074] In step 3), the stirring and mixing is performed at 50° C. for 8 hours; the alcohol washing is performed 4 times with anhydrous ethanol; the drying is performed at 110° C. for 3 hours; and the calcination is performed at 600° C. for 4 hours.

[0075] In step 3), the mass ratio of the intermediate, anhydrous ethanol and coupling agent is 15:60:3; the coupling agent is aluminate coupling agent DL411.

[0076] Comparative Example 1

[0077] Compared with Example 3, the difference in Comparative Example 1 is that step 2) does not involve a drying process, and the remaining components, preparation steps and parameters are the same.

[0078] Comparative Example 2

[0079] Compared with Example 3, the difference in Comparative Example 2 is that the drying temperature in step 2) is different. The drying in step 2) is performed at 100° C. for 1.5 h; the other components, preparation steps and parameters are the same.

[0080] Comparative Example 3

[0081] Compared with Example 3, the difference in Comparative Example 3 is that chitosan is not added, and the other components, preparation steps and parameters are the same.

[0082] Comparative Example 4

[0083] Compared with Example 3, Comparative Example 4 is different in that step 2) is not subjected to ultrasonic treatment, and the remaining components, preparation steps and parameters are the same.

[0084] The specific surface area, cobalt content and aluminum content of the aluminum-doped cobalt tetroxide obtained in Examples 1-4 and Comparative Examples 1-4 were calculated respectively, and the results are shown in Table 1.

[0085] Table 1

[0086] <![CDATA[Specific surface area (m 2 / g)]]> Aluminum content (%) Example 1 2.9 0.91 Example 2 3.0 0.93 Example 3 3.2 0.95 Example 4 3.0 0.92 Comparative Example 1 2.3 0.72 Comparative Example 2 2.5 0.76 Comparative Example 3 2.1 0.69 Comparative Example 4 2.3 0.73

[0087] From the test results in Table 1, it can be seen that compared with the comparative examples 1-4, the aluminum-doped cobalt tetraoxide obtained in the embodiments 1-4 of the present invention has a good aluminum-doped effect and has a higher specific surface area. Through the combined analysis and comparison of the embodiments 1-4, the comparative examples 1-4 and Table 1, it can be seen that the scheme of the present invention is to dry the cobalt hydroxide particles at a high temperature, so that they lose part of the free water and crystal water, and form more microporous structures. Under the action of ultrasound, chitosan is promoted to degrade to form small molecules and combine with cobalt hydroxide to form a self-assembled structure. Small molecules are more likely to enter the pore structure of cobalt hydroxide. Chitosan increases the contact between the aluminate coupling agent and the cobalt hydroxide particles through the action of hydrogen bonds and coordination bonds, and increases the grafting rate of the aluminate coupling agent. In addition, chitosan can also increase the pore structure of the cobalt hydroxide particles by roasting to generate cobalt tetraoxide. In the roasting process, a layer of aluminum oxide is doped on the surface of cobalt tetraoxide, which increases the thermal stability of cobalt tetraoxide, avoids the collapse of cobalt tetraoxide, increases its specific surface area, and promotes its formation of a large particle structure.

[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing large-particle aluminum-doped cobalt oxide, characterized in that: The preparation method comprises the following steps: Step 1) adding a strong alkali solution to a cobalt salt solution under stirring to perform a precipitation reaction, performing solid-liquid separation after the reaction is completed, washing to neutrality, and drying to obtain a preform; Step 2) drying the preform, mixing it in deionized water, adding chitosan, ultrasonically treating it, performing solid-liquid separation, and drying it to obtain an intermediate; Step 3) placing the intermediate in anhydrous ethanol, adding a coupling agent, stirring and mixing, and then performing solid-liquid separation, washing with alcohol, drying, and calcining to obtain aluminum-doped cobalt tetroxide.

2. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 1), the stirring is carried out at a rotation speed of 300-400 r / min; and the drying is carried out at a temperature of 70-80° C. to a constant weight.

3. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 1), the concentration of cobalt ions in the cobalt salt solution is 1.5-2.0 mol / L; the volume ratio of the cobalt salt solution to the strong alkali solution is 1:1; the cobalt salt solution is one or both of a cobalt chloride aqueous solution and a cobalt nitrate aqueous solution; and the strong alkali solution is a sodium hydroxide aqueous solution with a concentration of 1.0-1.5 mol / L.

4. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 2), the drying is performed at a temperature of 150-160° C. for 1.2-1.5 hours.

5. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 2), the ultrasonic treatment is performed at a frequency of 1000-1200 W and a temperature of 25-28° C. for 45-60 min.

6. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 2), the mass ratio of the preform, deionized water and chitosan is 8.0-8.5:900-1000:1.0-1.

3.

7. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 3), the stirring and mixing is performed at 40-50°C for 6-8h; the alcohol washing is performed 4 times with anhydrous ethanol; the drying is performed at 100-110°C for 2-3h; and the calcination is performed at 520-600°C for 3-4h.

8. The method for preparing large-particle aluminum-doped cobalt oxide according to claim 1, characterized in that: In step 3), the mass ratio of the intermediate, anhydrous ethanol and coupling agent is 12-15:50-60:2-3; the coupling agent is aluminate coupling agent DL411.

Citation Information

Patent Citations

  • Method for preparing cobaltosic oxide single-dimensional nano material

    CN101531403A

  • Method for preparing carbon-based hollow cobaltosic oxide

    CN107128979A

  • Aluminum-doped cobaltosic oxide core-shell material and preparation method thereof

    CN112723422A

  • Preparation method of hollow cobaltosic oxide nanoparticle / carbon composite material

    CN112850804A

  • Process for preparing activated carbon by using coconut shells as raw materials

    CN118356917A